BAKA’S STORY BY THE MAIN CHARACTER OF ANIME ONE PIECE EPISODE 1-10 - Ahmad Hakim; Arza Aibonotika; Sri Wahyu Widiati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: ThisThis study discusses baka utterances by the main character of one piece anime episode 1 – 10, the formulation of the problem in this study is how to analyze speech Baka By 10 Main Characters of One Piece Anime Episode 1 – 10. Conversational sentences in the data This research will be analyzed based on the function which is divided into two independent functions (Stand Alone) consisting of Explosive Interjections, oaths, curses, affirmations and contradictions,unfriendly suggestions, ritual insults, nicknames. The slot filler function consists of Adjective Enhancers, Adjectives of Dislike, stress, modal adverbial, use anaphoric epithets and supporting nouns. The data obtained in this study using Ljung's theory (2011) to find out the function of the word baka.Key Words: Baka's Story, Anime One piece , Ljung (2011)